Protection by exclusion? The (lack of) inclusion of adults who lack capacity to consent to research in clinical trials in the UK - Victoria Shepherd; Fiona Wood; Richard Griffith; Mark Sheehan; Kerenza Hood (Trials, 2019)
Abstract Background Around two million adults in the UK have significantly impaired decision-making capacity. However, there are concerns that this population is under-represented in research, due in part to the challenges around obtaining consent. Under-representation of populations denies those who would have wanted to participate the opportunity to make a contribution to society, but also fails to generate results that are applicable to them. Consequently, the evidence base for their care is poorer than for other populations. We recently published in this journal an analysis of Participant Information Sheets provided to consultees and legal representatives of adults who lack capacity and noted the small number of trials designed to include adults who lack capacity. In order to understand how many adults who lack capacity to consent are actually enrolled in clinical trials, we further explored how many of the participants lacked capacity, and who acted as a consultee or legal representative on their behalf. Main text The ISRCTN registry was searched for UK clinical trials in conditions commonly associated with cognitive impairment that were designed to include (or not exclude) adults who lack capacity to consent. Details about participants and capacity status were obtained from published data or directly from the trial teams. Of the 80 retrieved clinical trials that had completed in the previous 3 years, we identified 15 which included adults who lack capacity to consent. Data regarding participants’ capacity status were not available for five trials. Where capacity was reported, 5–100% participants lacked capacity to consent. Trials predominantly utilised personal consultees/legal representatives; however, 39% (634/1631) of participants required a professional to act as consultee/legal representative. Conclusions Only a small number of trials including adults who lacked capacity were identified. The majority of participants were represented by a personal consultee/legal representative; however, between 21 and 100% of participants across five trials required the involvement of a professional, suggesting it is not uncommon. Data relating to capacity status were rarely reported, potentially masking the under-representation of adults who lack capacity. The findings may help researchers and funders target resources towards studies involving under-represented populations to increase the much-needed evidence base for their care and treatment.